IMPACT OF CORTICOSTEROIDS ON PERINATAL OUTCOME - KSK, DIVYA; SAHITHI, BARLA KOMAL; GEDALA, VIVARNA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The study’s main aim was to demonstrate the efficacy of antenatal corticosteroids (betamethasone) to prevent respiratory distress syndrome (RDS) and other related complications in premature babies and to study the outcomes of neonates whose mothers received corticosteroids during the antenatal period. Methods: A total of 50 pregnant women with a risk of preterm delivery admitted to the labor ward of Prathima Institute of Medical Sciences were included in the study. It is a prospective, hospital-based, and longitudinal study. All women coming to the antenatal outpatient department of Prathima Institute of Medical Sciences who are at risk of preterm delivery were selected. The follow-up component of the study involved women identified as at high risk for premature delivery and who had received betamethasone. The neonatologist diagnosed the neonatal complications was taken as an outcome. Results: Of the 50 babies that were enrolled in the study, 27 (54%) were delivered by spontaneous vaginal delivery, 1 by assisted breech (2%), 1 by instrumental delivery (2%), and 18 (36%) were delivered by cesarean section. The occurrence of RDS among babies with low APGAR was 4 (44.44%). Only one intraventricular hemorrhage occurred among the category, with a low APGAR score (11.11%). Out of 19 cases, ten deaths were identified, and nine were alive within 24 h due to the action of steroids. Among 31 cases, two cases were death, and 29 were alive after 24 h of the duration of action of steroid. Even though mothers of all babies in this study admitted to the neonatal unit had received corticosteroids, there was still 24% mortality by 28 days. The results suggest that once admitted to NICU, having only received a single dose of corticosteroids <24 h previously (as opposed to more than 24 h), gestational age <34 weeks, and having any listed neonatal complications were associated with mortality by 28 days. Conclusion: Even though 50% of the neonates suffered complications, over 40% of the subjects were delivered before betamethasone could take effect. Several other factors, apart from betamethasone, influenced the outcome of neonates. The present study showed that the use of ANCS administration is the single most intervention to prevent complications of prematurity which can be done at a public health center or by a private practitioner, even in rural areas.